Metacognitive strategies improve self-regulation skills in expert sports coaches - Stanislav Sabaliauskas; Donatas Gražulis; Nelė Žilinskienė; Tomas Kaukėnas (Scientific Reports)
Abstract Self-regulation is linked to the ability to learn successfully, adapt to change, and project one’s future behavior. This study aims to evaluate the impact of metacognitive strategies on self-regulation skills in the creation of educational content. Nine expert sports coaches participated in the research, and a mixed-methodology research plan was used to conduct the research. The results highlight the transformative effects of metacognitive strategies on self-regulation skills and sports coaches’ experiences. The use of metacognitive strategies had a positive effect on the improvement of self-regulation skills. The facilitation program based on metacognitive questioning significantly affected the expert sports coaches’ self-reported self-regulation skills. The results of the thematic analysis revealed that coaches’ behavior was characterized by greater freedom in organizing their professional activities. Development of self-regulatory skills through changing educational practices encourages coaches’ curiosity and openness to innovation, recognition of otherness, broadening of horizons, understanding of complexity, and disclosure of connections.